2008
DOI: 10.1128/jvi.00169-08
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of V- or C-Defective Measles Viruses: Infection Control by the Inflammatory and Interferon Responses of Rhesus Monkeys

Abstract: Patients recruited in virus-based cancer clinical trials and immunocompromised individuals in need of vaccination would profit from viral strains with defined attenuation mechanisms. We generated measles virus (MV) strains defective for the expression of either the V protein, a modulator of the innate immune response, or the C protein, which has multiple functions. The virulence of these strains was compared with that of the parental wild-type MV in a natural host, Macaca mulatta. Skin rash, viremia, and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
99
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(110 citation statements)
references
References 55 publications
11
99
0
Order By: Relevance
“…Of note, a similar disparity has been found in studies on wild-type MVs of mild clinical virulence in rhesus monkeys, displaying slow kinetics of IL-4 mRNA levels in PBMCs (Devaux et al, 2008). As events in the immune induction of B-cell responses occur in lymph nodes, the local IL-4 response could give a different picture from that for PBMCs.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Of note, a similar disparity has been found in studies on wild-type MVs of mild clinical virulence in rhesus monkeys, displaying slow kinetics of IL-4 mRNA levels in PBMCs (Devaux et al, 2008). As events in the immune induction of B-cell responses occur in lymph nodes, the local IL-4 response could give a different picture from that for PBMCs.…”
Section: Discussionmentioning
confidence: 78%
“…The latter study based on blood leukocytes further identified early cytokine expression in animals within the first 7 days of eventually non-lethal infections (Svitek & von Messling, 2007). Also, analogous experiments with MV in monkeys have shown that wild-type viruses appear to control the early innate and antiviral responses in studies focusing on PBMCs during weeks 1 and 2 after infection (Devaux et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The P gene of Henipaviruses encodes at least three nonstructural proteins (C, V, and W) in addition to the P protein [33,34]; however, P protein is the only essential gene product for genome replication. The additional gene products are usually not required for virus replication in vitro, though they often serve as virulence factors in vivo [20,21].…”
Section: Aetiologymentioning
confidence: 99%